Developing Edu-Ecotourism as an Innovative Strategy for Community Empowerment in Social Forestry Program: Lessons from Gunungkidul Regency, Special Region of Yogyakarta - Wiyono, Wiyono; Subejo, Subejo; Sulastri, Endang (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
The Indonesian government is committed to implementing a social forestry program to ensure forest sustainability and improve community welfare. Community groups living near forest are granted permission to utilize forest resources, including timber, non-timber products, and environmental services such as ecotourism. This study aims to identify potential supporting resources and formulate strategies for developing edu-ecotourism within social forestry group in Gunungkidul Regency, Special Region of Yogyakarta. The study employs a qualitative method with a case study approach. Data collection was conducted through in-depth interviews, field observations, and documentation studies. This research was carried out at Sedyo Lestari Community Forest Farmer Group (SL-CFFG). The data were analyzed using the SWOT analysis model. The findings indicate that SL-CFFG has eight potential packages of learning materials to support edu-ecotourism development. These learning packages are derived from the group’s extensive experience in implementing social forestry programs under the community forestry scheme for over 20 years. These materials include: 1) Story telling of community forest management; 2) Forest land planning techniques; 3) Terracing techniques on forest land; 4) Teak replanting using a coppice system; 5) Agroforestry techniques; 6) Silvopasture techniques; 7) Nursery techniques; 8) Organic fertilizer production. Based on the SWOT analysis, four strategies for developing edu-ectourism in SL-CFFG were formulated: 1) Developing edu-ecotourism based on extensive experience, resources, and local wisdom in community forest management; 2) Establishing collaborations with multiple stakeholders to enhance human resource capacity, improve supporting facilities, and secure business capital; 3) Innovating sustainable edu-ecotourism management to adapt to changes in government policies and tourist behavior; 4) Building collaborative partnerships with tourism business and leveraging social media to enhance marketing and promotion networks.